Analysis of Learning Difficulties Based on Networking Communications During The Covid-19 Pandemic - Demayani Demayani (STAI Miftahul Ula Nganjuk, 2021)
This research aims to describe the difficulties of communication-based learning in the network (online) students of Class V of State Elementary School 119/IV Jambi City during the Covid-19 pandemic. The research method used is a descriptive qualitative method that produces and processes data that is descriptive. This research was conducted at SD Negeri 119/IV Kota Jambi on 29 class V students which was held on June 17-20, 2021. Data collection techniques through Google Form. The results obtained from this study show that the difficulties of learning communication in the network (online) experienced by students during the Covid-19 pandemic are not few and quite diverse. Learning is still considered less effective because there is no teacher who explains learning directly in the classroom and learning becomes less satisfactory to students' learning outcomes. Other obstacles experienced by students when online learning is implemented are difficulty understanding learning materials, constrained by quotas and internet networks, learning focus that is often distracted, the emergence of boredom and having to wait for parents to come home from work in order to learn because they do not have their own devices. For this reason, the role of parents and teachers is very important to realize optimal online learning results.